Application of The FRBR Concept in the Digital Library Catalog System Research and Development Agency of the Ministry of Home Affairs of The Republic of Indonesia - Septa, Septa; Mayesti, Nina (Edulib, 2021)
Library institutions have several very important elements, one of which is information retrieval which is currently used in the library's online catalog. The method for cataloging the online catalog is  Functional Requirements for Bibliographic  Records (FRBR). This  writing  aims  to  provide  an overview of the implementation of the FRBR structure in the online catalog of BPP Kemendagri digital library to simplify the information retrieval process and provide insights to those who access cataloged information. This research is a type of qualitative research with literature study, observation. Literature study is used for FRBR concepts and theories while observing as a user observes the digital library catalog belonging to BPP Kemendagri  by looking at the existing fields and then analyzed. The data were then analyzed using thematic analysis. The results of this study show that the online catalog display of the BPP Kemendagri digital library displays the relationship to the first group entity, namely the item entity, work, manifestation and expression and also has a relationship with the second group entity, namely the entity related to the party responsible for intellectual or artistic content, namely individuals or individuals. corporate body. The online catalog of BPP Kemendagri provides information and certain features related to content, language and physical descriptions, gives users access to other sources of information by clicking on the sections and the application of this FRBR has helped users search for information sources through information retrieval facilities.